Civil rights in America : a handbook of legal history - McLinden, Daniel, 1947- (Universal-Publishers, Inc., 2020)
"It's time for a textbook blending American history and American law. The key events and landmark cases found in these pages provide a candid look at civil rights in America -- pitting the American ideals of All men are created equal and Equal justice under law against a powerful enemy, white supremacy. Reading like a novel, American Civil Rights exposes racial inequality on American soil and the court rulings both for and against it. Clear, concise and informative -- the lessons here can be taught in a single semester in a Civil Rights class or in tandem with an American History class. Seldom does a book come along with a more gripping or timely subject matter. This textbook allows history teachers and students to explore the social and cultural impact of judicial thinking on society. The reading public in general can gain a profound understanding in short order of both America's history and legal decisions aimed at civil rights"--